How the Protein Architecture of RNases III Influences their Substrate Specificity? - Agüero-Chapin, Guillermin; Pérez-Machado, Gisselle; Collí Mull, Juan; Ancede-Gallardo, Evys; Antunes, Agostinho; A. de la Riva de la Riva, Gustavo (Current Pharmaceutical Design, 2016)
Background: The Ribonuclease III (RNase III) enzymatic class is involved in many important biological processes from bacteria to higher eukaryotes. Consequently, they have been useful as drug-target candidates for drug development. Despite their high molecular diversity, RNases III share common structural and catalytic features and some degree of enzymatic activity. However, the role of accessory domains as key determinants of substrate selectivity and over the biological function of each RNase III type is still under study. Results: The in vitro enzymatic activity of three RNase III members from class I (Escherichia coli RNase III, Schizosaccharomyces pombe Pac1 and Saccharomyces cerevisiae Rntp1) and the human Drosha placed in class II was revisited against four different substrates. These two RNase III classes comprise members showing different domain organization. Enzymatic activity differences were found among members of the class I, which were even higher when the human Drosha (class II) was tested. The substrate promiscuity of the E. coli RNase III was corroborated in vivo through its expression in S. cerevisiae, as reported previously, but was extended here to Pichia pastoris. The putative molecular mechanisms contributing for the lethal effect of the heterologous RNase III on the yeast lives were deeply discussed. Conclusion: The new generated biochemical data integrated with previous available information affirmed that RNases III substrate specificity as well as their cellular biological role is highly influenced by its protein structure architecture. This fact also allowed drawing evolutionary links between RNase III members from their structural and substrate specificity differences.
Keywords: Archetype